Analyzing Turnover Intention at PT Surya Karya Setiabudi: The Effects of Job Insecurity, Organizational Support, and Workload - Artha, Galih Nindi; Nuvriasari, Audita (LifeSciFi, 2025)
This study aims to examine the influence of job insecurity, organizational support, and workload on turnover intention among employees at PT Surya Karya Setiabudi. The background of this research lies in the growing concern over high employee turnover rates and the need to understand the factors that drive employees to consider leaving their jobs. The study employed a quantitative approach, involving 44 respondents selected through purposive sampling. Data collection was conducted using questionnaires, and instrument testing confirmed that the items used were both valid and reliable. To ensure the suitability of the regression model, classical assumption tests were conducted and indicated that the data was normally distributed, free from multicollinearity, and did not suffer from heteroscedasticity. The results of the analysis revealed that job insecurity does not have a significant impact on turnover intention, suggesting that employees may not consider job uncertainty as a primary reason to resign. Similarly, organizational support did not significantly affect turnover intention. However, workload was found to have a positive and significant effect, indicating that an excessive workload increases employees' intention to leave the organization. These findings highlight workload as the dominant factor influencing turnover intention.